2014
DOI: 10.1155/2014/681635
|View full text |Cite
|
Sign up to set email alerts
|

Differential Associations of Inflammatory and Endothelial Biomarkers with Disease Activity in Rheumatoid Arthritis of Short Duration

Abstract: Objectives. To estimate endothelial dysfunction in patients with rheumatoid arthritis (RA) of short duration in relation to disease activity based on the assessment of 28 joints (DAS28). Methods. We studied 29 patients (22 women, mean age 41 (SD, 9) years) with RA of short duration and 29 healthy controls. The RA subjects were divided into those with low (DAS28: 2.6–5.1, n = 18) or high (DAS28 > 5.1, n = 11) disease activity. Exclusion criteria included clinically overt atherosclerosis and other coexistent dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 53 publications
5
53
0
2
Order By: Relevance
“…CRP measurement has been suggested to be beneficial for estimating short term changes in disease progression in RA patients [12,13]. Several studies have reported increased CRP levels in patients with RA [4,14]. In the present study serum levels of both ADA and hsCRP were significantly elevated in RA patients compared to controls.…”
Section: Discussionsupporting
confidence: 53%
“…CRP measurement has been suggested to be beneficial for estimating short term changes in disease progression in RA patients [12,13]. Several studies have reported increased CRP levels in patients with RA [4,14]. In the present study serum levels of both ADA and hsCRP were significantly elevated in RA patients compared to controls.…”
Section: Discussionsupporting
confidence: 53%
“…29 IL-6 is increased in RA and even though it is not essential for bone resorption it may contribute to the increased bone resorption in RA. 30 In RA and in other chronic inflammatory conditions, not only bone resorption but also bone formation is affected. The increase in TNF-a during inflammation induces an increase in dickkopf-1 (DKK-1), which is a negative regulator of the Wnt pathway.…”
Section: Inflammatory Diseases Immune System and Bonementioning
confidence: 99%
“…Recent studies with RA patients have indeed revealed interactions between ED and disease activity; these include soluble human vascular cell adhesion protein 1, von Willebrand factor, pentraxin-3, asymmetric dimethyl-L-arginine, soluble E-selectin, monocyte chemotactic protein-1, and osteoprotegerin. 33 Many of these substances are affected by inflammatory mediators and cytokines, and as specified earlier, contribute to the mechanisms underlying RA pathogenesis. With respect to therapeutic strategies for RA treatment, especially anti-tumor necrosis factor-alpha therapies, most are effective at reducing inflammation, as well as improving endothelial function.…”
Section: Discussionmentioning
confidence: 86%